Therapeutic role of neem (Azadirachta indica Adr. Juss.) in different types of cancer: A systematic review - Azam, Husnain; Khan, Muhammad Tahir; Lodhi, Madeeha Shahzad; Sadiqa, Ayesha; Yasin, Tayyaba (International Journal of Applied and Experimental Biology, 2023)
Azadirachta indica constituents exhibit potential therapeutic role to control cancer progression. The potential anti-cancerous activity of neem extracts reduces cell propagation, migration, inflammation, and invasion. The current review describes the importance and effectiveness of neem extracts in different solvents against various cancers. Studies performed in different geographic locations from 2001 to 2021 were searched in Google, PubMed, Google Scholar, and NCBI. The relevant information has been retrieved, including the type of extracts, solvents, year of publication, and type of cancers. A total of 125 relevant studies published in different journals have been screened, among which the most commonly used neem part was leaf (n = 79), followed by seed (n = 18), flower (n = 10), oil (n = 10), bark (n = 10), roots (n = 6), fruit (n = 6), gum (n = 5), limonoids (n = 5), nimbolide (n = 4), stem (n = 4), xylem (n = 1), and as herb (n = 1). Similarly, the most commonly investigated cancer to be treated with the neem extract was breast cancer (n = 23), followed by cancerous cell lines (n = 21), prostate cancer (n = 11), and leukemia (n = 8). Most of the studies applied ethanol (n = 40) as a solvent for neem extraction, followed by methanol (n = 25), distilled water (n = 17), ethyl acetate (n = 6), Gibco Dulbecco’s Modified Eagle Medium (n = 4), 7,12-dimethylbenz[a]anthracene (n = 4), MTT assay (n = 3), acetone (n = 3), ether (n = 3), ethyl alcohol (n = 2), hexane (n = 2), glucose (n = 2), oxadiazol-2yl-benzothiazole (n = 2), and N-nitrosodiethylamine (n = 1). In conclusion, neem is an important medicinal plant with therapeutic potency against different types of cancer. However, its role has not been investigated widely in some cancers, including bone cancer, retinoblastoma, and oral cancer. Moreover, its potential role may be enhanced if nanocarriers are conjugated to prevent them from human enzymatic metabolism and for successful targeted delivery in cancer therapy.